Optimization Compresion Strength Of Concrete Using The Deterministic System With Simpleks Method - Handayani, Tri; Mandasari, Febry; Ellysa, Ellysa; Pranata MH, Andi Asnur (Sean Institute, 2022)
Scientific computing is the field of science that studies mathematical models and quantitative analysis related to involving the use of computersto assist planners in making decisions. The purpose of this research is to determine the compressive strength of concrete with 2 samples of normal concrete specimens that have K-200 and K-300 quality. This research method is carried out by conducting direct research in the laboratory and optimizing concrete compressive strength with the deterministic system of the simplex method. The Simplex method is used to find the optimal value of a linear program that involves many constraints and many variables (more than two variables). Based on the results of research in the laboratory, the K-200 quality concrete compressive strength of 167 kg / cm2 and K-300 quality concrete obtained 195 kg / cm2 compressive strength, while based on the data obtained through optimization with the simplex method it is known that for K-200 concrete quality a compressive strength of 116.5 kg / cm2 was obtained with material requirements of cement 10.56 kg, water 2.11 kg, fine aggregate 31.73 kg and coarse aggregates 13.05 kg. For K-300 quality concrete, compressive strength is 648.6 kg / cm2 with material requirements cement 2.4 kg, water 1.62 kg, fine aggregate 20.15 kg and crude aggregate 25.04 kg. The value of compressive strength in K-300 concrete is due to the amount of coarse aggregate material used which is much greater than the mix design, which is 25.04 kg. With the magnitude of the compressive strength value followed by the magnitude of material requirements reaching 2 times greater when compared with the results of mix design